2023
DOI: 10.1021/acscatal.3c00363
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the Interface of Dual Active Sites to Enhance Higher Oxygenate Synthesis from Syngas with High Activity

Abstract: Selective synthesis of higher oxygenates from syngas provides a promising route for the conversion of nonpetroleum carbon resources into valuable chemicals. However, it remains a grand challenge to design highly efficient and stable dual-sites structures to promote the production of higher oxygenates. Herein, we reported an effective method to maximize the interface of dual active sites via designing the structure of alloy carbide derived from the FeCo layered double hydroxide precursor. Cobalt atoms were well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Even so, suffering from limited solubility, phase separation seems to be inevitable in bimetallic catalysts. For this reason, interfacial Co 0 –CoO x , and Co 0 –Co 2 C were constructed from Co-spinel, where Co δ+ is active for nondissociative CO adsorption. By tailoring MSI, the ratio of Co 0 /Co δ+ in Co 0 –CoO x can be tuned .…”
Section: Progress On Spinel Catalysts For Thermal-driven C1 Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, suffering from limited solubility, phase separation seems to be inevitable in bimetallic catalysts. For this reason, interfacial Co 0 –CoO x , and Co 0 –Co 2 C were constructed from Co-spinel, where Co δ+ is active for nondissociative CO adsorption. By tailoring MSI, the ratio of Co 0 /Co δ+ in Co 0 –CoO x can be tuned .…”
Section: Progress On Spinel Catalysts For Thermal-driven C1 Conversionmentioning
confidence: 99%
“…Experiments and theory calculations indicated that the superior activity of MnGaO x -spinel over a solid solution catalyst can be attributed to its higher reducibility (higher concentration of oxygen vacancies) and the presence of coordinatively unsaturated Ga 3+ sites, which facilitates the dissociation of CO. 114 Even so, suffering from limited solubility, phase separation seems to be inevitable in bimetallic catalysts. For this reason, interfacial Co 0 −CoO x 115,116 and Co 0 − Co 2 C 117−119 were constructed from Co-spinel, where Co δ+ is active for nondissociative CO adsorption. By tailoring MSI, the ratio of Co 0 /Co δ+ in Co 0 −CoO x can be tuned.…”
Section: Introductionmentioning
confidence: 99%
“…%, based on bimetallic phase diagrams , ) usually causes severe dealloying and sintering under reaction conditions for catalysts exclusively formed by the two metals (labeled as M 1α M 2β , with α:β denoting the molar metal ratio, Figure ). Families with enhanced solubility between metals like the Co-Fe system have also been explored, with the belief that the MS functionality is provided by Co carbides formed during operation . In this case, performance is still limited by the sintering of active metals, reducing the density of surface sites.…”
Section: Introductionmentioning
confidence: 99%
“…Families with enhanced solubility between metals like the Co-Fe system have also been explored, with the belief that the MS functionality is provided by Co carbides formed during operation. 22 In this case, performance is still limited by the sintering of active metals, reducing the density of surface sites.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al prepared a series of CoFe alloy catalysts that efficiently hydrogenated CO 2 into jet-fuel-range hydrocarbons [22]. Gong et al designed a CoFe alloy catalyst derived from an FeCo hydrotalcite precursor [23]. They observed the formation of (Fe x Co y )C with an abundant Co-Fe contact boundary, which promoted the formation of an oxygenate.…”
Section: Introductionmentioning
confidence: 99%